2001
DOI: 10.1063/1.1391476
|View full text |Cite
|
Sign up to set email alerts
|

Moment analysis of hydrated electron cluster spectra: Surface or internal states?

Abstract: Moment analysis is applied to the absorption spectra of size-selected water anion clusters measured by Ayotte and Johnson [J. Chem. Phys. 106, 811 (1997)], to extract the radius of gyration and the kinetic energy for the unpaired electron. Implications for the surface versus interior binding model controversy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
90
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 16 publications
25
90
1
Order By: Relevance
“…24 Instead, they proposed that the spectroscopy of the hydrated electron was more consistent with a solvent−anion complex, 24 a structure which shares many features in common with the LGS simulations. 15 Indeed, moment analysis of the hydrated electron's absorption spectrum tells us that the hydrated electron's charge density has a radius of gyration of 2.4 Å, 25 but nothing in the spectrum directly indicates whether the water molecules are primarily inside or outside of the charge density.…”
Section: ■ Controversy Over Hydrated Electron MD Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Instead, they proposed that the spectroscopy of the hydrated electron was more consistent with a solvent−anion complex, 24 a structure which shares many features in common with the LGS simulations. 15 Indeed, moment analysis of the hydrated electron's absorption spectrum tells us that the hydrated electron's charge density has a radius of gyration of 2.4 Å, 25 but nothing in the spectrum directly indicates whether the water molecules are primarily inside or outside of the charge density.…”
Section: ■ Controversy Over Hydrated Electron MD Simulationsmentioning
confidence: 99%
“…For example, experiment has shown that the hydrated electron has a radius of gyration of 2.45 Å, 25 respectively (all calculated without the use of Ewald summation, which is known to slightly alter these values 13,19 ). ).…”
Section: ■ Comparing Different Hydrated Electronmentioning
confidence: 99%
“…13,29 Specifically, it was shown that the computed trends in the radius and the kinetic energy of the excess electron with cluster size for SB clusters reproduce the tendencies extracted from experiments. 30 Up to now, this is the strongest (and most intriguing) evidence in favor of strong surface-bound excess electronic states in water cluster anions. 13,29 Several recent ab initio quantum chemical studies have also appeared in the literature adding substantially to the debate on both sides.…”
mentioning
confidence: 99%
“…The assignment of the experimentally available data 27,32,33,44,45 to these isomers still generates intense debates. 22,23,32,41,44,76,77 Therefore, it is important to anticipate and examine physical properties that are potentially different in these two states. Here we observe that the two types of cluster isomers relax with significant differences, interior state cavity type clusters relaxing more efficiently than surface cluster…”
Section: Discussionmentioning
confidence: 99%
“…in interior or surface excess electronic states. 21,22,23,32,41,42,43,44,45 Since it is plausible that the main character of the relaxation is different in different localization modes, simulations of electron localization and/or electronic excitation in water cluster anions may provide clues on how to distinguish these isomers experimentally.…”
Section: Introductionmentioning
confidence: 99%